PENGARUH STRES KERJA DAN KETERLIBATAN KERJA TERHADAP TURNOVER INTENTION YANG DIMEDIASI OLEH KEPUASAN KERJA MASA PANDEMI COVID-19 PADA PERAWAT RSUD ZAINAL ABIDIN BANDA ACEH - Lulu Wifaq Yumna; Ridwan Ibrahim (Departemen Manajemen, 2021)
This study aims to measure the effect of work stress and work involvement on turnover intention mediated by job satisfaction during the covid-19 pandemic on nurses at Zainal Abidin Hospital, Banda Aceh. The sampling technique used was simple random sampling. Amounting to 115 respondents. The data collection used in this study was a questionnaire. Hierarchical Linear Modeling is used as an analytical method to determine the effect of all the variables involved. The results showed that the variables of job stress, job involvement, and job satisfaction significantly impact turnover intention. Job stress and job involvement have a substantial effect on job satisfaction. Job satisfaction partially mediates the impact of job stress on turnover intention and the impact of job involvement on turnover intention.